Intravenous methylprednisolone pulse therapy for children with epileptic encephalopathy - Pera, Maria Carmela (Funct Neurol, 2015)
The aim of this retrospective study of children affected by epileptic encephalopathy was to evaluate seizure frequency, electroencephalographic pattern and neuropsychological status, before and after intravenous methylprednisolone therapy. Eleven children with epileptic encephalopathy were administered one cycle of intravenous methylprednisolone (15–30 mg/kg/day for three consecutive days, once a month for four months) in addition to constant dosages of their regular antiepileptic drugs. The treatment resulted in statistically significant reductions of generalized slow spike-and-wave discharges (p<0.0028) and seizure frequency (p<0.013), which persisted even after methylprednisolone pulse therapy was stopped. A globally positive outcome was noted in 9/11 patients (81.8%). This methylprednisolone treatment regimen did not cause significant or persistent adverse effects. We suggest that children with epileptic encephalopathy without an underlying structural lesion could be the best candidates for intravenous methylprednisolone pulse therapy.